Korupcja w III RP – obszary szczególnego występowania - Borowiec, Piotr (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
This analysis of the phenomenon of corruption draws the Author to a conclusion that efficient struggle against corruption is futile unless good law is originated and exacted appropriately. This law should be created by competent individuals and on the basis of substantive and credible information eliminating ‘pathological lobbying’. At the same time, politicians who create Polish law need to realize that they are themselves also obliged to observe this law and admit that corruption to a large degree concerns them personally.